'Going Missing' as a Maladaptive Coping Behavior for Adults Experiencing Strain. Issue 1 (2nd January 2022) - Huey, Laura; Ferguson, Lorna
ABSTRACT: This study applied the Threat Appraisal and Coping Theory to explore the mechanisms influencing a person to go missing. We examined the negative emotions and stressors – proximate stressors/stressful events, underlying life stressors, emotional states, and other dysfunctional behaviors – of adults who were reported as missing from 2014–2018. Our results indicate that missing persons experience significant underlying life stressors, stressful situations, and proximate stressors that can 'trigger' a missing episode. We also found that most missing adults are described as facing negative emotions, such as anger, and engaging in maladaptive behaviors, such as drug and alcohol use, that are related to these events. These findings, we suggest, highlight that affectual and individual-level mechanisms are influential factors contributing to why adults go missing. Lastly, it was revealed that missing adults are commonly reported as experiencing strains and stressors in their personal relationships, indicating that this phenomenon may be attenuated through social support as an adaptive coping resource. Through these results, we can begin to understand missingness as driven by a negative event, stressor, or emotion in which the person engages in the maladaptive coping behavior of 'going missing' as a way to escape the situation and achieve some level of emotional or cognitive distance.